The Impact of Technology in Mathematics Education: A Case Study of Pakistan - M. Arif Hussain,; Mujeeb Ahmed Khan,; Shaheen Abbas, M. Ilyas and Bulbul Jan,; M. Rashid Kamal Ansari, (Journal of Basic & Applied Sciences, 2021)
As we know that computers have become fountain pens of twenty first century. This paper discusses Computer Algebra System (CAS)activities used as part of a study conducted by the authors using Mathematica. It also emphasizes the use of Matlab for students and researchers for the purpose of verification of results of the problems at hand. This study will attempt to show the positive effect of the use of technology on students’ motivation by taking three examples from calculus, advanced algebra and sequence and series problems. The graphic illustration of functions helps students towards a proper understanding of mathematical science problems. The work carried out will be useful for students, researchers, and teachers understand both theory and use of computer applications in order to become master of the subject.